Challenges of teaching in higher education in medicine during the SARS-CoV-2 pandemic (Research, Society and Development, 2022)
The present study aims to evaluate the perception of professors about remote teaching in medicine during the COVID-19 pandemic. Articles that met the following criteria were included: Studies published in English, Portuguese and Spanish, between the years 2019 to 2022, whose theme was related to the core question of the research. Articles that presented duplicity, lack of conclusive results or some inconsistency with the central theme were excluded from the research, such as: (1) Presentation of perceptions that extrapolated the teaching view on the analyzed issue and (2) Remote teaching in the active modality aimed at area of ​​health that do not encompass medicine. In this integrative literature review, five articles published between 2019 and 2022 were selected, which were included by previously defined criteria. Of these, one was found via the Virtual Health Library (VHL) and four via MEDLINE. From the analyzed literature, this integrative review was able to evaluate different aspects about the perception of medical professors about the modalities of remote teaching, it was noticed that the transition to the virtual environment, because it is a sudden change, caused in first moment, evident concern in the teaching staff about aspects such as the receptivity of students to new teaching methods and, above all, about their adaptation to online education methodologies, since many professionals did not have previous experience with the digital environment. However, from the establishment of various mechanisms of action, the satisfaction of these professionals with the implementation of digital study methods was noticeable.